The Associations Between Sleep Duration and Various Metabolic Health Indices Among Adults in the United States: A Multivariate Analysis of Variance (MANOVA) Using National Health and Nutrition Examination Survey (NHANES) 2021 to 2023 Dataset - Shuo Feng; Jeong-Hui Park; Qiyue Zhang; Ping Ma; Jung-Min Lee; Jong Cheol Shin (Journal of Primary Care & Community Health)
Objective: This study explores the associations between various sleep durations and metabolic health indices, including systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol levels, high-density lipoprotein (HDL) cholesterol, and waist circumference. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) 2021 to 2023, were analyzed. MANOVA and Bonferroni-adjusted ANOVAs were conducted to examine the relationships between sleep duration (sleep deprivation (≤5 h), short sleep (5-7 h), recommended sleep (7-9 h), and long sleep (>9 h)) and metabolic health indices. Results: MANOVA revealed significant group differences between sleep duration and metabolic health indices, with Wilks’ Lambda (Λ) = .98, F (3, 5095) = 4.26, P  < .001. Compared to recommended sleep duration, both sleep deprivation and short sleep were associated with higher DBP ( P s < .01) and waist circumference ( P s < .001), and lower HDL levels ( P s < .05) Long sleep was associated with lower HDL levels ( P  < .01) and lower total cholesterol ( P  < .01). Conclusion: The study highlights the detrimental associations of both sleep deprivation and short sleep with metabolic health, such as elevated blood pressure and waist circumference, and lowered HDL cholesterol. Long sleep may also negatively impact metabolic health by reducing HDL.